2018
DOI: 10.1093/mnrasl/slx205
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Geminid meteor shower activity

Abstract: Mathematical modelling has shown that activity of the Geminid meteor shower should rise with time, and that was confirmed by analysis of visual observations 1985-2016. We do not expect any outburst activity of the Geminid shower in 2017, even though the asteroid (3200) Phaethon has a close approach to Earth in December of 2017. A small probability to observe dust ejected at perihelia 2009-2016 still exists.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…For the statistical analyses of the meteor pairs' existence, the shower activity is necessary to be known. Ryabova & Rendtel (2018) showed that the activity of the Geminid meteor shower is increasing for the last 30 years. According to Figure 3 in this paper, the visual ZHR was between 130 and 140 in 2006.…”
Section: Geminid Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…For the statistical analyses of the meteor pairs' existence, the shower activity is necessary to be known. Ryabova & Rendtel (2018) showed that the activity of the Geminid meteor shower is increasing for the last 30 years. According to Figure 3 in this paper, the visual ZHR was between 130 and 140 in 2006.…”
Section: Geminid Activitymentioning
confidence: 99%
“…The age of the stream is no longer that few thousand years. Its activity is increasing in the last few decades (Ryabova & Rendtel 2018). Jenniskens (2006) suggests that it will reach its maximum around 2050.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most reliably active meteor shower events, the Geminid stream has been extensively observed and characterized using several methodologies (Jenniskens, 2006). Ryabova (1999) estimated the age of the stream to be less than a few thousand years, which was corroborated by Beech (2002) who placed constraints of 1000 − 4000 yr. A series of papers has used radar and video observations to construct a detailed model of the structure of the stream (Ryabova, 2007(Ryabova, , 2012(Ryabova, , 2016(Ryabova, , 2017Ryabova and Rendtel, 2018). The ejection velocity was calculated using the apparent width at 1 au by Ryabova (2016) to be 1 km s −1 .…”
Section: Introductionmentioning
confidence: 99%
“…A few prominent streams, such as the well-known Geminid meteoroid stream, are easily detectable and have been studied for decades (e.g. Denning 1893;Plavec 1950;Whipple 1983;Jones et al 2016;Hui & Li 2017;Ryabova & Rendtel 2018, and many others). However, most of the Sun-approaching streams are weakly active and have not received a lot of attention (Ye 2018).…”
Section: Introductionmentioning
confidence: 99%